Control Strategy of Dual-motor Nutation Coupling Drive System for Electric Bus - Cheng Pan; Ligang Yao; Junlin Lai; Can Cai; Xinxin Chen (Jixie chuandong)
In order to reduce the energy consumption of pure electric vehicles and improve the driving range of electric vehicles， a new dual-motor nutating dynamic coupling system is taken as the research object， and a control strategy with the minimum electric power as the target is proposed. Based on the entire control strategy framework， the control strategy is divided into upper， middle， and lower layers. The upper control strategy is the calculation of demand torque. According to the driver's intention， road information， battery information， etc.， the vehicle's demand torque is accurately obtained. The middle control strategy is drive mode division and power distribution. The mode division is based on the vehicle speed as the logical threshold and the minimum electric power as the target to develop a dual-motor speed and torque distribution strategy to achieve dual-motor power system power distribution. The lower-level control strategy is mode switching process control. In order to reduce the power drop of mode switching， in the process of switching from single motor mode to dual motor mode， power reduction processing is adopted. Finally， a simulation model of dual-motor dynamic coupling system is established in Matlab/Simulink， which verifies the reliability of the control strategy.